Ethnobiological Classification : Principles of Categorization of Plants and Animals in Traditional Societies. - Berlin, Brent (Princeton : Princeton University Press, 2014)
A founder of and leading thinker in the field of modern ethnobiology looks at the widespread regularities in the classification and naming of plants and animals among peoples of traditional, nonliterate societies--regularities that persist across local environments, cultures, societies, and languages. Brent Berlin maintains that these patterns can best be explained by the similarity of human beings' largely unconscious appreciation of the natural affinities among groupings of plants and animals: people recognize and name a grouping of organisms quite independently of its actual or potential.
Frontmatter -- Contents -- Preface -- PART ONE: Plan -- CHAPTER ONE. On the Making of a Comparative Ethnobiology -- CHAPTER TWO. The Primacy of Generic Taxa in Ethnobiological Classification -- CHAPTER THREE. The Nature of Specific Taxa -- CHAPTER FOUR. Natural and Not So Natural Higher-Order Categories -- PART Two: Process -- CHAPTER FIVE. Patterned Variation in Ethnobiological Knowledge -- CHAPTER SIX. Manchúng and Bíkua: The Nonarbitrariness of Ethnobiological Nomenclature -- CHAPTER SEVEN. The Substance and Evolution of Ethnobiological Categories -- References -- Author Index -- Index of Scientific Names -- Index of Ethnoscientific Names -- Subject Index
Print version record.
Cover.
eBooks on EBSCOhost
Keywords: Folk classification -- Cross-cultural studies; Ethnozoology; Ethnobotany; Ethnobotany; Classification anthropologique -- Études transculturelles; Ethnozoologie; Ethnobotanique; SOCIAL SCIENCE -- Anthropology -- General; SCIENCE -- Life Sciences -- Biology; Ethnobotany; Ethnozoology; Folk classification; Cross-cultural studies